Impact of single‐nucleotide polymorphisms in DNA repair pathway genes on response to chemoradiotherapy in rectal cancer patients: Results from ACCORD‐12/PRODIGE‐2 phase III trial. Issue 11 (31st May 2019) - Boige, Valérie; Mollevi, Caroline; Gourgou, Sophie; Azria, David; Seitz, Jean‐François; Vincent, Marc; Bigot, Ludovic; Juzyna, Beata; Miran, Isabelle; Gerard, Jean‐Pierre; Laurent‐Puig, Pierre
Abstract : We examined whether 66 germline single‐nucleotide polymorphisms (SNPs) in 10 candidate genes would predict clinical outcome in 316 patients with resectable locally advanced rectal cancer (LARC) enrolled in the ACCORD‐12 phase III trial who were randomly treated with preoperative radiotherapy plus capecitabine (CAP45; n = 155) or dose‐intensified radiotherapy plus capecitabine and oxaliplatin (CAPOX50; n = 161). The primary endpoint was tumor response according to the Dworak score. Multivariate logistic regression models adjusted on treatment arm and T stage determined the SNPs prognostic and predictive values for tumor response. In univariate analysis, five SNPs in ERCC2, XPA, MTHFR and ERCC1 were associated with the Dworak score in the CAPOX50 arm. In the overall population, interaction with treatment arm was significant for ERCC2 rs1799787 ( p interaction = 0.05) and XPA rs3176683 ( p interaction = 0.008), suggesting a predictive effect for response to oxaliplatin‐based chemoradiotherapy (CRT). All but XPA rs3176683 had a prognostic effect on tumor response. In a multivariate model, interaction remained significant for XPA rs3176683 ([OR 7.33, 95% CI 1.40–38.23], p interaction = 0.018) and the prognostic effect significant for ERCC2 rs1799787 ([OR 0.55, 95%CI 0.32–0.93], p = 0.027) and ERCC1 rs10412761 ([OR 0.57, 95%CI 0.34–0.98], p = 0.042). Patients with the T/G haplotype of rs1799787 and rs10412761 had a 60% decrease in odds of response ( p < 0.001). None of the five SNPs were associated with toxicity, overall and disease‐free survival. These data suggest that genetic variation in DNA repair genes influences response to preoperative CRT in LARC and identify patients who benefit from the addition of oxaliplatin to CRT. Abstract : What's new? May germline variants in genes encoding DNA repair and detoxification enzymes predict response to preoperative capecitabine‐based chemoradiotherapy in rectal cancer? In response, the authors analyzed 66 germline variants of 10 candidate genes. Among them, ERCC1 rs10412761 and ERCC2 rs1799787 are associated with tumor response in patients treated with preoperative capecitabine‐based chemoradiotherapy. For the first time, they described a predictive effect of XPA rs3176683 that may identify patients who benefit from adding oxaliplatin to capecitabine‐based chemoradiotherapy.